The Effect of Financial Performance and Corporate Governance on Extensive of Disclosure Sustainability Reporting - Indah Permata Dewi; Arrum Safitri; Saprilia Tri Lestari (LAFADZ JAYA Publisher, 2023)
This study aims to analyze the influence of the determinants of disclosure sustainability reporting. The determinants of sustainability reporting classified are financial performance and corporate governance. Financial performance includes company size, profitability, leverage and liquidity. Corporate governance includes the board of directors and audit committee. The data used in this study is secondary data in the form of sustainability report data, annual report and financial statements companies registered on Asia Sustainability reporting Rating (ASRRAT) in 2018-2021 by purposive sampling methods. This study uses a quantitative approach to the method of analysis using multiple linear regression tests.